2019
DOI: 10.2147/dmso.s156270
|View full text |Cite
|
Sign up to set email alerts
|

<p>Measurement of diabetes, prediabetes and their associated risk factors in Myanmar 2014</p>

Abstract: Background Myanmar, a low-income Southeast Asia country with an estimated population of 53.9 million, is currently facing an increasing burden of noncommunicable diseases. Research that systematically measures and reports the national prevalence of diabetes and prediabetes within Myanmar represents a gap in the literature. This study, a national survey, was conducted with the objectives of 1) measuring diabetic population, 2) measuring the prediabetic population, and 3) finding out the risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
3
20
2
Order By: Relevance
“…Consistent with previous studies, subjects with an older age had a higher risk of DM in our study [ 14 16 ]. Participants with PDM were also older than the normal participants, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies, subjects with an older age had a higher risk of DM in our study [ 14 16 ]. Participants with PDM were also older than the normal participants, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to previous studies [ 14 , 18 , 29 , 30 ], higher systolic blood pressure was found to be associated with a higher risk of both DM and PDM in our study. The pathophysiological mechanisms that explain the association between hypertension and DM include high BP-induced microvascular dysfunction and altered endothelial dysfunction, which have been found to be independent predictors of type 2 diabetes [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…A diabetes-screening programme may be introduced, particularly targeting the older age high-risk groups. 26 Some studies found an association between psychosocial distress, such as suicidal behaviour, 15,16 stress 17,18 and passive smoking, 19 increased the likelihood of diabetes, while in this study only in unadjusted analysis alcohol family problem was associated with diabetes, while the stress of family member die from suicide, suicidal ideation and passive smoking were not signi cantly with prediabetes and/or diabetes.…”
Section: Discussioncontrasting
confidence: 55%
“…12,13 The lack of PA is the fourth leading risk factor for global mortality, despite the known hazards of being sedentary, PA levels continue to fall worldwide. 14 Such physical inactivity crisis is serious in Yangon, which is very urban but its city structure is incompletely urbanized un-favouring active transportation and PA.…”
Section: Introductionmentioning
confidence: 99%